2013
DOI: 10.1149/05701.1831ecst
|View full text |Cite
|
Sign up to set email alerts
|

An SOFC Cathode Infiltrated with Pr6O11

Abstract: We fabricated single cells with an 8YSZ electrolyte, a Pt anode, a spin-coated Ce0.8Sm0.2O1.9 (SDC) cathode buffer layer and a LaNi0.6Fe0.4O3 (LNF) cathode infiltrated with mixed conductor of Pr6O11. The cathode performance was investigated by the ac impedance method at 800oC. The initial interface resistance of the Pr6O11 infiltrated cathode was reduced to about one seventeenth of that without the infiltration. The interface resistance increased slightly with 106 mA/cm2 current loading. It increased faster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Here, it is assumed that the mixed valence of the praseodymium cations in Pr6O11 is likely to be responsible for such a high efficiency toward the oxygen reduction reaction. Previous works [8], [9], [10] reported the beneficial effect of Pr6O11 as additive in oxygen electrode but all these results did not lead to polarization resistances as low as those measured here. [22], Sm0.5Sr0.5CoO3-δ infiltrated into SDC [23], and La0.6Sr0.4CoO3-δ infiltrated into GDC [24].…”
Section: Electrochemical Measurements On Symmetrical Cellssupporting
confidence: 43%
See 1 more Smart Citation
“…Here, it is assumed that the mixed valence of the praseodymium cations in Pr6O11 is likely to be responsible for such a high efficiency toward the oxygen reduction reaction. Previous works [8], [9], [10] reported the beneficial effect of Pr6O11 as additive in oxygen electrode but all these results did not lead to polarization resistances as low as those measured here. [22], Sm0.5Sr0.5CoO3-δ infiltrated into SDC [23], and La0.6Sr0.4CoO3-δ infiltrated into GDC [24].…”
Section: Electrochemical Measurements On Symmetrical Cellssupporting
confidence: 43%
“…It is also interesting to note that few recent studies have reported an improvement of the electrochemical performance when using Pr6O11 as additive in composite electrodes made for instance of LNF (LaNi0.6Fe0.4O3-δ) or LSM (La0.8Sr0.2MnO3)-GDC, either mixed or infiltrated with Pr6O11 [8], [9], [10], [11]. Then, with respect to these features, it becomes mandatory to examine the exact role played by this simple oxide from an electrochemical viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the presence of the residual phase, Pr 6 O 11 , might actually improve the cell performance. Indeed, few authors have already reported that decorating an electrode surface with Pr 6 O 11 improves the solid-gas reaction and leads to a decrease of the polarization resistance [22][23][24], suggesting that it has interesting catalytic properties. Here, the association of the ionic and electronic conductivities of Pr 2 NiO 4+δ and the catalytic activity of Pr 6 O 11 could induce a decrease of the polarization resistance of the cell.…”
Section: Eis Measurements On Symmetrical Cellsmentioning
confidence: 99%
“…Rare-earth oxides are also popular in the field of high-temperature solid-state electrochemistry and in particular for solid oxide fuel cells (SOFCs). For example, Pr 6 O 11 has been reported to enhance electrochemical ORR performance when used as an additive in composite oxygen electrodes: Pr 6 O 11 -infiltrated LaNi 0.6 Fe 0.4 O 3-δ (LNF) electrodes exhibited improved performance over LNF (LaNi 0.6 Fe 0.4 O 3-δ ) electrodes, as reported by Chiba et al [48] and Ding et al [49]. More recently, polarization resistances as low as 0.026 Ω cm 2 at 600 • C were reported for a pure Pr 6 O 11 columnar-type cathode prepared by electrostatic spray deposition (ESD) [50].…”
Section: Introductionmentioning
confidence: 56%